2004
DOI: 10.1063/1.1682689
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer study of FeCoSiAlGaPCB amorphous alloys

Abstract: A Mössbauer spectrometry and magnetic study have been performed on FeCoSiAlGaPCB amorphous alloys in order to get information about the variations in the atomic short range order with the substitution of Fe by Co. The decrease of the Curie temperature with decreasing Fe content was analyzed in the framework of the molecular field theory. The average hyperfine magnetic field at 77 K decreases linearly with increasing Co content as does the average magnetic moment per transition metal atom and a linear dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…These plots can be described as two overlapped peaks (bimodal behaviour): one, almost independent of the composition, is centred around 10 T, whereas the other peak maximum shifts from 17 to 27 T as Co content increases in the alloy. This bimodal character and a similar compositional dependence were also observed for other Co containing amorphous Fe-based alloy series [11,12]. The high H region of the distributions must be due to Fe surrounded by Fe and Co atoms, preferentially.…”
Section: Amorphous Samplessupporting
confidence: 49%
See 1 more Smart Citation
“…These plots can be described as two overlapped peaks (bimodal behaviour): one, almost independent of the composition, is centred around 10 T, whereas the other peak maximum shifts from 17 to 27 T as Co content increases in the alloy. This bimodal character and a similar compositional dependence were also observed for other Co containing amorphous Fe-based alloy series [11,12]. The high H region of the distributions must be due to Fe surrounded by Fe and Co atoms, preferentially.…”
Section: Amorphous Samplessupporting
confidence: 49%
“…Although similar linear correlations have been reported for amorphous and crystalline alloys [11,20], it is worth noticing that, in this study, the linear correlation between <H> and < TM > is observed for systems with different amount of crystalline and amorphous phases, characterized by the value of X C . Figure 7 clarifies this point.…”
Section: Comparison With Saturation Magnetization Measurementsmentioning
confidence: 52%
“…20 It is worth mentioning that, in contrast to this behavior, amorphous alloys with larger metalloid concentration exhibit a monotonous decrease of T C am with increasing Co content. [21][22][23] In the case of the studied alloys, Co addition leads to an increase of the ͉⌬S M pk ͉ value, unlike the observed behavior for the FeCoSiAlGaPCB alloy series, with larger metalloid content. 17 It has to be noted that an estimate of the error in ͉⌬S M pk ͉ is below 3%, which is below the differences observed for both samples.…”
Section: Resultsmentioning
confidence: 57%
“…The explanation of this influence of the metalloid content on T C am and ͉⌬S M pk ͉ should be ascribed to the change in the local environment of Fe and Co atoms and its effect on the exchange interaction between atoms. 23 The ͉⌬S M pk ͉ value of the Cocontaining Nanoperm-type alloy is ϳ50% larger than that of a Mo-containing Finemet-type alloy, with a comparable T C am , measured under the same experimental conditions, 14 while the Co-free Nanoperm-type alloy increases the peak entropy change by ϳ31% with respect to the same Finemet-type alloy. Comparing with the Fe 70 B 5 C 5 Si 3 Al 5 Ga 2 P 10 amorphous alloy, 17 the Co-containing alloy presents a comparable value of ͉⌬S M pk ͉, with the advantage of a peak temperature T pk , which is 100 K closer to room temperature for the alloy studied in the present work.…”
Section: Resultsmentioning
confidence: 91%
“…This result can be mainly ascribed to the decrease of the exchange interaction between Co-Co pairs provoked by the presence of metalloid atoms. 29 The Curie temperature and the coercive field are affected by structural relaxation processes: 31 T C increases as the annealing temperature increases and H C decreases monotonically as the relaxation progresses. The lowest coercivity, H C (min), obtained after annealing the samples for 30 min at temperatures between 713 and 733 K, decreases as the Co and B content of the alloy increases ͓Fig.…”
Section: B Magnetic Propertiesmentioning
confidence: 99%